1984
DOI: 10.3109/02813438409018083
|View full text |Cite
|
Sign up to set email alerts
|

Early Rehabilitation at Home of Elderly Patients with Hip Fractures and Consumption of Resources in Primary Care

Abstract: From 1976 onwards an active rehabilitation programme has been applied to elderly patients with fresh hip fractures at the Department of Orthopaedics in Lund in Southern Sweden. This involves early mobilisation in the hospital (internal fixation and immediate weight-bearing) and at home, rehabilitation in cooperation with primary health care personnel from the time of the patient's admission. The purposes of this investigation were to evaluate the effect of this programme in primary care and to assess the consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…The rehabilitation program only temporarily increases the need for home-help service (7). Before the fracture, 30 percent of the patients had home help, and after the fracture 40 percent had home help.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The rehabilitation program only temporarily increases the need for home-help service (7). Before the fracture, 30 percent of the patients had home help, and after the fracture 40 percent had home help.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The rehabilitation scheme has been presented elsewhere (Ceder 1980, Jamlo et al 1984. All the surviving patients were visited in their own home at 1,2, and 4 months postoperatively by primary health care personnel, usually the district physiotherapists.…”
Section: ~A L ------~------~mentioning
confidence: 99%
“…Choong et al [8] reported that discussion of the treatment process and goals with the patient, the patient's family, and the medical staff led to shortening of the hospitalization period. In addition, early exercise with weight-bearing on the affected leg [9] and shortening of the hospitalization period [10] are effective approaches for functional recovery, as well as being of benefit financially.…”
Section: Introductionmentioning
confidence: 99%